Monitoring Computer Activities with Cloud to Device Messaging (C2DM) - Suwitno Witno; Rino Rino (Tech-E, 2018)
In a particular division, a supervisor needs to perform monitoring of the activities carried out at his employers to improve the performance of the work of his subordinates. Leaders are often not in place to monitor the activities of his subordinates in carrying out their responsibilities. One solution to overcome these problems is to supervise the use of their computer by means of push notification. By utilizing the technology of Cloud to Device Messaging (C2DM), supervisor can monitor computer activities of his employers anywhere. Given this research, is expected to help the supervisor in monitoring his employers despite not being in place. This may indirectly improve performance in a division. For further research can be developed monitoring in a real time.